Le lieu propre du néant - Pamela Bianchi (Sillages Critiques)
For Rachel Whiteread, the void has a shape, and nothingness occupies a place. The British artist solidifies specific volumes of air (the interior of bottles, the space surrounding a mattress, the interior space of a room, a house, etc.); in doing so, she highlights the emergence of absence. The original object disappears and a new form appears, a kind of simulacrum which is neither trace nor ruin, but a liminal and monumental object. As a form of positivist deconstruction, the object disappears by returning in the form of an archetypal image, as a new object to contemplate. Through the analysis of some of her works, this paper deepens the concepts of vestige, trace, and contemporary anti-monumentality.